The Role of the National Human Rights Commission (Komnas HAM) in Addressing Contemporary Violations (Contemporary Issues on Indonesian Human Rights Law and Policy, 2025)
This paper analyzes the role of Indonesia’s National Human Rights Commission (Komnas HAM) in addressing contemporary human rights violations in the country. Established in 1993, Komnas HAM is tasked with monitoring and investigating human rights abuses, providing recommendations to the government, and advocating for victims. The paper explores Komnas HAM’s institutional evolution, its effectiveness in addressing violations such as land grabbing, religious intolerance, and police brutality, and the challenges it faces in promoting human rights in a complex political environment. Through an analysis of recent case studies, including the 2018 Papua conflict and the treatment of religious minorities, the paper assesses the commission's impact on policy changes and public awareness. Interviews with human rights activists, government officials, and Komnas HAM staff reveal tensions between the commission’s independent role and its dependency on state resources, as well as the broader political context that limits its power. The study concludes by offering recommendations to strengthen Komnas HAM’s effectiveness, such as increased funding, political autonomy, and enhanced public engagement.